2008
DOI: 10.1051/limn:2008019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of stable carbon and nitrogen isotopes within the pelagic food web of Taihu Lake

Abstract: Particulate organic matter (POM), dissolved organic matter (DOM), bacteria and cladoceran were sampled seasonally at Zhihugang Estuary and Lake Center in Taihu Lake. The δ 13 C of the four organic matter fractions showed consistent temporal variation, with heaviest values in summer and lower at other times of the year. The cladoceran δ 13 C showed a significant correlation with that of POM, reflecting a heavy dietary dependence on POM during the study period. The bacteria became enriched in 13 C compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Further, both temperate streams and lakes tend to experience seasonal strong pulses of allochthonous inputs (e.g. fallen leaves, terrestrial invertebrates [46][47][48]). These trends combined mean that, relative to estuarine and marine communities, freshwater food webs may experience high turnover in both community composition and productivity [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Further, both temperate streams and lakes tend to experience seasonal strong pulses of allochthonous inputs (e.g. fallen leaves, terrestrial invertebrates [46][47][48]). These trends combined mean that, relative to estuarine and marine communities, freshwater food webs may experience high turnover in both community composition and productivity [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Food-web studies in lakes often focus on the pelagic habitat. These studies have demonstrated that the stable isotope ratios at the base of food webs often vary seasonally [7][8][9] and spatially within and between lakes. [10] For example, studies on algae demonstrated large changes in δ…”
mentioning
confidence: 99%
“…In addition, the 15 N enrichment in eutrophic lakes may also be due to the contributions of urban wastes from surface runoff which is an important source of nitrogen to lakes (Carpenter et al, 1998) and is typically enriched with 15 N. For example, Lake Taihu in central China is a large urban lake influenced by high human population in the watershed. Anthropogenic disturbances to this lake can be illustrated by high d 15 N of DIN and POM (Xie et al, 2007;Zeng et al, 2008). Savage (2005) Figure 4 may be due to the presence of microzooplankton and/or inputs from human wastes.…”
Section: Influences Of Non-algal Materials From Autochthonous and Allmentioning
confidence: 99%